2012
DOI: 10.1016/j.jvs.2012.03.243
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin improves vascular function of arteriovenous fistula in a diabetic rat model

Abstract: Arteriovenous (AV) fistula is the most common vascular access for hemodialysis in patients with end-stage renal disease. Studies have shown that blood flow in the AV fistula is significantly reduced in patients with diabetes and the period for maturation of an AV fistula is longer in these patients. The underlying mechanisms of AV fistula failure in diabetes are still poorly understood and there are limited therapeutic approaches that can increase the lifespan of these fistulas. The present study demonstrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 36 publications
1
22
0
1
Order By: Relevance
“…Since there was no previous control study investigating the vascular protective effect of statins on the AV fistulas of subjects with DM, we conducted a series of experimental studies testing the therapeutic potential of the water-soluble HMG-CoA reductase inhibitor rosuvastatin on the function of AV fistulas in diabetic rats. Our recent report demonstrated that rosuvastatin improves the blood flow and endothelial function of the arterial limb of the AV fistula in diabetic rats by attenuating the generation of tissue superoxide anions [11]. The current study extends the investigation of the protective effect of rosuvastatin from the arterial limbs to the venous sites of the AV fistula.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Since there was no previous control study investigating the vascular protective effect of statins on the AV fistulas of subjects with DM, we conducted a series of experimental studies testing the therapeutic potential of the water-soluble HMG-CoA reductase inhibitor rosuvastatin on the function of AV fistulas in diabetic rats. Our recent report demonstrated that rosuvastatin improves the blood flow and endothelial function of the arterial limb of the AV fistula in diabetic rats by attenuating the generation of tissue superoxide anions [11]. The current study extends the investigation of the protective effect of rosuvastatin from the arterial limbs to the venous sites of the AV fistula.…”
Section: Discussionsupporting
confidence: 62%
“…Animals underwent procedures to create a fistula in the aorta and adjacent inferior vena cava (IVC) to form an AV fistula as previously described in our reports [11,14]. Rats were anesthetized with inhaled isoflurane (2-3% v/v in oxygen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Encontram-se iniciativas de manter os vasos com a mesma conformação e avaliar os resultados de outros fatores, como drogas para inibir a proliferação da neo-íntima ( Aschberg et al 1976;Roan et al 2012). …”
Section: Discordâncias Com Outros Trabalhosunclassified